Menuju Sosiologi Nusantara: Analisa Sosiologis Ajaran Ki Ageng Suryomentaram dan Amanat Galunggung - El-Zastrouw, Ngatawi (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2020)
The discourse on indigenizing of social sciences has been popular among Indonesian scholars since 1970s. However, it has not shown any significant development, in spite of many writings of Nusantara scholars that can be bases of references to develop sociological theories of Nusantara, such as the manuscripts of Kawruh Jiwo Ki Ageng Suryomentaram and Amanat Galunggung. Making an effort to indigenize social sciences of Nusantara, the present study investigates both manuscripts. The results of the study argue that there are basic theories of sociology discussed in those two manuscripts. For example, the concepts of social integration (kabuyutan), division of labor, and historical consciousness, which are discussed in the manuscript of Amanat Galunggung. The sociological perspective of Amanat Galunggung is very similar to the structural-functional theory. While, the concepts found in Kawruh Jiwo Ki Ageng Suryomentaram, such as the concepts of four division of human being, feeling (rasa) and intention (karep), and reciprocal relations between human and society. Those theories are genuine and authentical; and if the theories are developed, they will result in a typical of Nusantara sociological theory. Keywords: Indigeneus, Kramadangsa, Rasa, Kabuyutan, Tri Tangtu REFERENCE Alatas, S.F., (2010), Diskusus Alternatif Dalam Ilmu Sosial Asia, Tanggapan Terhadap Eurocentrisme, Bandung, Mizan, Anthony Giddens (1997), Central Problem in Social Theoty, Berkeley & Los Angeles: University of Callifornia Press. Ary, H. Gunawan (2000), Sosiologi: Suatu Analisis Sosiologi tentang Pelbagai Problem Pendidikan, Cet. I; Jakarta: Rinika Cipta. Astrid S. Susanto (1979) Pengantar Sosiologi dan Perubahan Sosial, Bandung, Binacipta. Allice S. Rossi (ed.), 1985, Sosiology and Antropoly in the Peopleâ€™s Republic of China, National Academy Press, Washington DC.; Bacthiar Wardi (2010). Sosiologi Klasik Dari Comte hingga Parsons. Bandung: Remaja Rosdakarya. Bento, Ted dan Ian Craib (2009). Filsafat Ilmu Sosial Pendasaran Filosofis Bagi Pemikiran Sosial. Yogyakarta: Ledalero. Budiman, Arif (1991), Negara dan Pembangunan; Study tentang Indonesia dan Korea Selatan, Jakarta Yayasan Padi Kapas. Chambliss, Rollin (1954), Social Thought, New York, Dryden Press; Danasasmita, S. (1987). Sewaka Darma, Sanghyang Siksakandang Amanat Galunggung. Bandung: BP3 Kebudayaan Sunda Depdikbud; Drapper, Hal, (1978) â€œKarl Marxâ€™s Theory of Revolution The Politics of Social Classes,â€ Vol. II, Monthly Review Press, Faruk.(2010), Pengantar Sosiologi Sastra, dari Strukturalisme Genetik sampai Post Strukturalisme.Yogyakarta: Pustaka Pelajar Heri Santoso, (1997), Dimensi Epistemoligis Dalam Indegenisasi Ilmu-Ilmu Sosial di Indonesia, Jurnal Edisi Khusus; hal. 188 dikutip dari https://media.neliti.com/media/ publications/228423-dimensi-epistemologis-dalam-indeginisasi-022d80a4.pdf, diakses pada 5 Agustus 2020. Jacson, Karl D. and Lucian Pye (ed.), Political Power and Communication in Indonesia, Berkeley and Los Angles, University of California Press. Jatman, Darmanto, (2000). Psikologi Jawa, Yogyakarta, Bentang Budaya; ———————-, (2008), Ilmu Jiawa Kaum Pribumi (Indigeneus Psycology, Pidato Pengukuhan Guru Besar Psikologi Undip Johnson, Doyle Paul (1986), Teori Sosiologi Klasik dan Modern, jilid 1 dan 2 (terj. Robert M.Z. Lawang), Jakarta, Gramedia Noorduyn dan A. Teew, Tiga Pesona Sunda Kuno, terj. Hawe Setiawan, Jakarta: Pustaka Jaya, Jones, (2003) Pengantar Teori-Teori Social: Dari Teori Fungsionalisme Hingga Post-Modernisme, (trj.Saifuddin), Jakarta: Pustaka Obor Ki Fudyartanto, (2002), Psikologi Kepribadian Timur, Yogyakarta: Pustaka Pelajar; Kuntowijoyo, (1990) Paradigma Islam; Interpretasi Untuk Aksi, Bandung, Mizan; —————, , (2001), Muslim tanpa Msjid, Bandung, Mizan; Lubis, N. H. (2013). Sejarah Kerajaan Sunda.Bandung: Yayasan MSI; Masâ€™ud, Mochtar (1994), Politik Birokrasi dan Pembangunan, Yogyakarta, Pustaka Pelajar Mills, C. Wright and Hans Gerth, (1956), From Max Weber; Essays in Sociology, New York, Oxford University Press; Nasiwan dan Yuyun Sri Wahyuni (2016), Seri Teoti-Teori Sosial Indonesia, Yogyakarta, UNY Press, Prihartanti, (2004) Kepribadian sehat menurut konsep Suryomentaram, Surakarta: Muhammadiyah University Press; Rangga Saptya Mohamad Permana, Makna Tri Tangtu di Buana Yang Mengandung Aspek Komunikasi Politik Dalam Framen Carita Prahyangan, Jurnal Kajian Komunikasi, Volume 3, No. 2, Desember 2015 Ratih Suryowiyono (2007), Ki Ageng Suryomentaram Sang Plato dari Jawa, Yogyakarta: Cemerlang Publishing, Schutz, Alfred dan Thomas Luchmann, (1973), the Structure of the Life-World, Evanston, III; Northwetern University Press, Soerjono Soekanto, (1985), Sosiologi Suatu Pengantar , Cet. V; Jakarta: CV Rajawali, Sri Teddy Rusdi (2014), Epistemologi Ki Ageng Suryomentaram, Tandhesan Kawruh Bab Kawruh Jakarta: Yayasan Kertagama; Suaedy, Ahmad (2018), Gusdur, Islam Nusantara dan Kewarganegaraan Bineka, Jakarta, Gramedia Pustaka Utama; Sugiarto, Ryan, (2015), Psikologi Raos; Saintifikasi Kawruh Jiwo Ki Ageng Suryomentaram, Yogyakarta, Pustaka Ifada Sumaryono, E. (1999). Hermeneutik: sebuah metode filsafat. Yogyakarta: Kanisisus Suryomentaram, Grangsang (1990), Kawruh Jiwa, jilid 1-4, Jakarta: CV. Haji Masagung, Suryalaga, H.R. Hidayat, (2010), Rawayan Jati Kasundaan, (Bandung, Yayasan Nurhdayah, Turner, Jonathan H. (1990), The Strucrure of Sosiological Theory, Belimont, California, Wadsworth Publishing Company Weber, Max (1947), The Theoty of Social and Economic Organzation, New York, Free Press and McMillan Publishing Company. Sumber Internet https://id.usembassy.gov/id/education-culture-id/program-fulbright-id/, diakses tanggal 17 Agustus 2020 https://id.usembassy.gov/id/amerika-serikat-berikan-satu-juta-dolar-dana-penelitian-untuk-enam-ilmuwan-indonesia/, diakses pada 5 Agustus 2020 https://id.usembassy.gov/id/amerika-serikat-dan-indonesia-resmikan-lima-pusat-kerjasama-penelitian-berkualitas-tinggi-di-indonesia/, diakses pada 5 Agustus 2020